2002
DOI: 10.1093/emboj/21.3.470
|View full text |Cite
|
Sign up to set email alerts
|

A cyclophilin functions in pre-mRNA splicing

Abstract: We report that the cyclophilin USA-CyP is part of distinct complexes with two spliceosomal proteins and is involved in both steps of pre-mRNA splicing. The splicing factors hPrp18 and hPrp4 have a short region of homology that de®nes a high af®nity binding site for USA-CyP in each protein. USA-CyP forms separate, stable complexes with hPrp18 and hPrp4 in which the active site of the cyclophilin is exposed. The cyclophilin inhibitor cyclosporin A slows pre-mRNA splicing in vitro, and we show that its inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
99
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 31 publications
3
99
0
5
Order By: Relevance
“…Of note is that inhibition studies with the PPIase inhibitor cyclosporin A did not provide strong evidence for a requirement of this activity in pre-mRNA splicing in vitro (17). However, in vivo studies revealed that PPIase activity is required for splicing (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note is that inhibition studies with the PPIase inhibitor cyclosporin A did not provide strong evidence for a requirement of this activity in pre-mRNA splicing in vitro (17). However, in vivo studies revealed that PPIase activity is required for splicing (17).…”
Section: Discussionmentioning
confidence: 99%
“…However, in vivo studies revealed that PPIase activity is required for splicing (17). The role of cyclophilins in pre-mRNA splicing in vitro, which takes at least 1 h may be masked by the relatively fast spontaneous isomerization of the prolyl bond.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are clear evidences demonstrating that most cyclophilins are PPIases (40), and thus may play an important role in protein folding, it has also been suggested that cyclophilins may also act as chaperones, binding to peptide sequences containing proline residues (50 -52). Interestingly, studies that support this view also show that CsA impairs the chaperone activity of the cyclophilin and thus the secretion of the target protein (53). It is conceivable that CypB plays an auxiliary role as a molecular chaperone that traffics through the entire secretory pathway in association with ADAMTS13.…”
Section: Discussionmentioning
confidence: 97%
“…Cyclophilins are proteins that are widely distributed and abundantly found in eukaryotic and prokaryotic systems and are present in the cytosol as well as in the nucleus (Wang & Heitman, 2005). Extensive studies of various model organisms have suggested that cyclophilins are involved directly or indirectly in a wide range of cellular processes, including cell division (Schreiber, 1991), transcriptional regulation (Shaw, 2002), protein trafficking (Price et al, 1994), cell signalling (Freeman et al, 1996;Duina et al, 1996), pre-mRNA splicing (Horowitz et al, 2002), molecular chaperoning (Schmid, 1993;Weisman et al, 1996) and stress tolerance (Andreeva et al, 1999;Dominguez-Solis et al, 2008). They are known to possess peptidylprolyl cis-trans isomerase (PPIase) enzymatic activity, a reaction that is believed to be involved in the late stages of protein folding (Takahashi et al, 1989;Gö thel & Marahiel, 1999).…”
Section: Introductionmentioning
confidence: 99%